Ligand-based in silico Approach for Identifying Potent Antidotes Against Botulinum Neurotoxin Serotype A, B, E, and F - Agnihotri, Surabhi; Kushwah, Vinita; Dhaked, Ram Kumar (Journal of Current Toxicology and Venomics, 2025)
IntroductionBotulinum neurotoxins are the most poisonous substances reported and listed in category ‘A’ of biowarfare agents. As serotype identification is a time-consuming process and there is no antidote commercially available, the development of inhibitors against serotypes causing human botulism would be beneficial. In the present study, a ligand-based in silico method was applied to identify the “hits” that could have the potential to act as countermeasures against human-intoxicating BoNTs.MethodsFor this purpose, a computational approach using Molegro Virtual Docker and AutoDock tools was performed, where around thirty-five derivatives were designed and docked into the catalytic domain of BoNT/A, B, E, and F. The designed compounds were also studied for their ADME properties using an online web tool.Results and DiscussionAnalysis of the molecular docking data of the complex by Molegro Virtual Docker revealed a high binding affinity between the target and designed ligands, with the MolDock score between -139.85 and -88.24 kcal/mol, whereas the AutoDock score ranged between -11.65 and -5.30 kcal/mol. Three SMNPIs, A11, A18, and A20, exhibited better binding affinities with the target proteins BoNT/A, /B, E, and /F and could be potential pan-active inhibitors. The ADME/T study showed that the designed ligands were less toxic and possessed drug-resemblance properties by considering the Lipinski, Ghose, Veber, and Egan rules, with a bioavailability score of 0.56.ConclusionOur study provides insight into ‘hits’, which can lead to further progress in experimental studies and the development of new antidotes for botulism.
Keywords: Molecular docking